Neoadjuvant anti-programmed death-1 immunotherapy by pembrolizumab in resectable non-small cell lung cancer: results of the NEOMUN trial - Eichhorn, Martin E.; Niedermaier, Benedikt Walter; Charoentong, Pornpimol; Klotz, Laura Valentina; Baum, Philip; Griffo, Raffaella; Allgäuer, Michael; Stenzinger, Albrecht; Bischoff, Helge; Schneider, Marc; Christopoulos, Petros; Haberkorn, Uwe; et al. (Journal for ImmunoTherapy of Cancer, 2025)
Background The phase II NEOMUN trial was conducted to investigate the therapeutic effect of preoperative programmed death receptor-1 inhibitor pembrolizumab for treating non-small cell lung cancer (NSCLC). Herein, we report the final efficacy, safety, and long-term survival results.Methods Patients with resectable stage II/IIIA NSCLC were included. Two cycles of pembrolizumab (200 mg intravenously once every 3 weeks) were administered before surgery. The primary objectives were to assess the feasibility and safety of neoadjuvant treatment and evaluate antitumor activity. We analyzed the clinical parameters and pathologic, radiological, and metabolic tumor response data.Results 29 patients with NSCLC were enrolled. NSCLC histology revealed adenocarcinoma and squamous cell carcinoma in 24 and in 5 patients, respectively. 93.1% of patients were treated with two therapy cycles. 73 adverse events were reported, of which 18 were treatment-related. Complete tumor resection rate was 100%. Major (≤10% vital tumor cells) and complete pathologic response rates were 24.1% and 13.8%, respectively. Tumor response increased with higher programmed death-ligand 1 tumor proportion scores (TPS) and high pretherapeutic tumor mutational burden (≥10 mut./Mb). The metabolic response, quantified non-invasively using positron emission tomography/CT, predicted the pathologic tumor response. The disease-free survival was 75.9% at 24 and 36 months, and the overall survival was 82.7% at 24 and 36 months.Conclusions Neoadjuvant immunotherapy with pembrolizumab appears safe and feasible and is associated with a remarkable major pathologic response rate. Preoperative TPS, change in maximal standardized uptake value during the induction phase, and high mutational burden might be suitable clinical parameters for predicting pathologic response in surgical candidates.Trial registration number NCT0319746.